The Effect Of Workload And Work Environment Toward Workers Performance In Dinas Energi Dan Sumber Daya Mineral Daerah Provinsi Sulawesi Utara During Covid-19 Pandemic - Christbarth Maindoka; Sifrid S Pangemanan; Maria V. J Tielung (Universitas Sam Ratulangi, 2022)
The conditions of workers that can get heavy workload and need to face work environment also have other aspect that need to be considered in form of Covid-19 pandemic that happen currently. In the current situation; these workers need to work in an unprecedented condition. The main problem within this paper is regarding the employee performance that can be affected by workload and work environment, not only with those 2 aspects but the existence of Covid-19 pandemic that still looming until now create new layers of problems that may affect the performance of workers. This study is a quantitative study and uses multiple linear regression method. The findings of this study shows that the independent variables which are Workload and Work Environment simultaneously affect the Workers Performance. Workload and Work Environment act as separate independent variables also affect the Workers Performances. Based on the result, the researcher provided several recommendations which are: superiors are expected to give sufficient amount of workload to every employee, meaning that workload cannot be higher than the capability of the workers. Also, further improvement in terms of facilities can be done by the company.